Pra Rancangan Camping Ground Dan Glamping Puncak Cubodak Dengan Pendekatan Konsep Wisata Halal: Halal Tourism - Suci Ramadhani; Titin Sundari; Hendri Silva (JURNAL TEKNIK, 2020)
Puncak Cubodak is in Kampar regency, precisely on Jalan Lintas Bangkinang-Payakumbuh, Tanjung Alai, XII Koto Kampar, Kampar regency. Is one of the tourist attractions that have views of green hills, ‘island’ which is surrounded by Danau PLTA Koto Panjang. So far, Puncak Cubodak has only been used for tourism photographs, it is unfortunate if the potential of Puncak Cubodak is only enjoyed only by taking pictures. Therefore, the step to develop the Puncak Cubodak is to add accommodation facilities in the form of camping and glamping areas. And also applying the concept of tourism that is also developing in Indonesia, namely the concept of Halal Tourism. Halal Tourism here is more applicable to Muslim-friendly tourism and availability of halal food and prayer place. The purpose of this paper is to obtain a design concept with a research method in the form of a Puncak Cubodak environmental analysis, user analysis, and building analysis. The results obtained from the analysis are the design concept with the approach to the concept of halal tourism in the form of images. With this design concept, it is hoped that it can develop Puncak Cubodak tourism and the concept of halal tourism can be more widely recognized by thepublic, especially in Pekanbaru.